Islamic Values and Their Role in Strengthening a Civilized Democracy - Dalimunthe, Tua; Hutabarat, Sri Wulan; Harahap, Elisma; Harahap, Yenni Fitriyani (Business Finence Analyst Co.,, 2025)
Democracy in Muslim-majority societies is frequently debated in relation to religious values, particularly regarding the compatibility between Islam and democratic principles. This study examines the role of Islamic values in strengthening civilized democracy in the Indonesian context, where democratic practices are shaped by both Pancasila and Islamic ethical traditions. Employing a qualitative conceptual approach through systematic literature analysis, this study reviews classical Islamic teachings, key scholarly works on political Islam, and Indonesia’s historical and contemporary democratic experiences. The findings demonstrate that fundamental Islamic values such as justice (‘adl), consultation (shura), social responsibility, and brotherhood (ukhuwwah) are conceptually aligned with democratic principles including participation, equality, and accountability. Historically, early Islamic governance reflected consultative and participatory practices, while in Indonesia these values are institutionally embodied in Pancasila, particularly the principle of deliberation. The study further reveals that current democratic challenges in Indonesia, including money politics, identity polarization, and weak law enforcement, are not merely institutional but also ethical. Islamic values therefore provide a moral framework that strengthens democracy beyond procedural mechanisms. This study concludes that integrating Islamic ethical principles with democratic institutions contributes to the development of a civilized, inclusive, and morally grounded democracy in Indonesia.